Electrodeposited high strength, thermally stable spectrally selective rhenium nickel inverse opals. Issue 31 (27th July 2017) - Zhang, Runyu; Cohen, Joseph; Fan, Shanhui; Braun, Paul V.
Abstract : We demonstrate the first 3D ReNi inverse opal formed using low temperature electrodeposition and report superior material properties that could be interesting for applications under harsh environments. Abstract : Rhenium–Nickel (Re x Ni100− x ) based 3D metallic inverse opals (IOs) were realized via colloidal crystal templated electrodeposition from an aqueous electrolyte. By varying the electrodeposition parameters, x could be varied from 0 to 88. Under reducing conditions, the rhenium-rich IOs were structurally stable to temperatures of at least 1000 °C for 5 h and for at least 12 h after coating with a thin layer of Al2 O3 . This demonstrated level of thermal stability is significantly improved compared to previously reported electrodeposited refractory inverse opals with similar characteristic dimensions. A strong frequency dependence in the optical reflection, which ranged from ∼5% around 1.5 μm to ∼65% around 5 μm, is predicted by simulations and experimentally observed, indicating the potential of this structure as a high temperature spectrally selective optical absorber/emitter. The elastic modulus of the ReNi IO structure is ∼35 GPa and the hardness is ∼0.8 GPa. Both these properties are much higher than those of Ni inverse opals and other periodically porous materials with similar characteristic pore dimensions. We suggest this work provides a promising approach for thermally stable mesostructured materials for high temperature catalyst supports, refractory photonics and mechanical applications including high temperature filtration, and high temperature actuators.